Teaching Media in the Teaching of Arabic Language to Non-Native Arabic Speakers - Abdullah, Rais (IAIN Samarinda, 2016)
Learning media has demonstrated its superiority in helping educators or teachers in the process of conveying the message of learning more quickly and easily caught by the students. The media play a role in enriching the learning experience of students, increase their attention to the lesson, minimize differences in perception between teachers and students as well as to help resolve personal differences between students. The teaching Arabic to non-native speaker would be more interesting and easier to learn, remembered, understood and practiced by the students, if taught through the media. This article aims to explore the benefits, importance and role of instructional media in teaching Arabic to non- native Speaker